The Bdellovibrio bacteriovorus twin-arginine transport system has roles in predatory and prey-independent growth - Chang, Chien-Yi; Hobley, Laura; Till, Rob; Capeness, Michael; Kanna, Machi; Burtt, William; Jagtap, Pratik; Aizawa, Shin-Ichi; Sockett, R. Elizabeth (Society for General Microbiology, 2011)
Bdellovibrio bacteriovorus grows in one of two ways: either (i) predatorily [in a host-dependent (HD) manner], when it invades the periplasm of another Gram-negative bacterium, exporting into the prey co-ordinated waves of soluble enzymes using the prey cell contents for growth; or (ii) in a host-independent (HI) manner, when it grows (slowly) axenically in rich media. Periplasmic invasion potentially exposes B. bacteriovorus to extremes of pH and exposes the need to scavenge electron donors from prey electron transport components by synthesis of metalloenzymes. The twin-arginine transport system (Tat) in other bacteria transports folded metalloenzymes and the B. bacteriovorus genome encodes 21 potential Tat-transported substrates and Tat transporter proteins TatA1, TatA2 and TatBC. GFP tagging of the Tat signal peptide from Bd1802, a high-potential iron-sulfur protein (HiPIP), revealed it to be exported into the prey bacterium during predatory growth. Mutagenesis showed that the B. bacteriovorus tatA2 and tatC gene products are essential for both HI and HD growth, despite the fact that they partially complement (in SDS resistance assays) the corresponding mutations in Escherichia coli where neither TatA nor TatC are essential for life. The essentiality of B. bacteriovorus TatA2 was surprising given that the B. bacteriovorus genome encodes a second tatA homologue, tatA1. Transcription of tatA1 was found to be induced upon entry to the bdelloplast, and insertional inactivation of tatA1 showed that it significantly slowed the rates of both HI and HD growth. B. bacteriovorus is one of a few bacterial species that are reliant on a functional Tat system and where deletion of a single tatA1 gene causes a significant growth defect(s), despite the presence of its tatA2 homologue.